Pengaruh E-WOM Pada Media Sosial Terhadap Keputusan Berkunjung Wisatawan Gen Z Ke Kawasan Strategis Pariwisata Daerah Canggu - Saraswati, Nyoman Galuh Narendraswari; Widana, Ida Bagus Gede Agung; Liestiandre, Hanugerah Kristiono (Journal of Tourism and Creativity, 2024)
This study aims to determine the effect of e-wom variables, including the dimensions of intensity, positive valence, negative valence, and content, partially or simultaneously on the decision to visit Gen Z tourists in the Canggu KSPD. The population in this study were domestic tourists, generation Z, with a sample size of 322 respondents using a non-probability sampling technique. Data collection was carried out through a survey method using a research instrument in the form of a questionnaire. The analysis technique used is multiple linear regression analysis. The results of this study indicate that there is an influence of the e-WOM dimensions of intensity, positive valence, negative valence, and content, which have a significant effect partially and simultaneously.